PENGARUH MEDIA KULTUR PISANG LOKAL TERNATE TERHADAP FEKUNDITAS LALAT BUAH (DROSOPHILA MELANOGASTER MEIGEN 1979) STRAIN NORMAL - Widya Safira Waimahing; Chumidach Roini; Nurmaya Papuangan; Suparman Suparman (UNIVERSITAS KHAIRUN, 2022)
Drosophila melanogaster is one of the most common fruit fly species. This study aims to see the effect of culture media on the fecundity of these flies. The culture media used were pisang raja, pisang mulut bebek and pisang mas. The study was preceded by catching and identifying fruit flies, making culture media, making parent stock, isolating pupae to mating on each culture medium and counting the number of pupae. Data were analyzed using ANOVA. The results showed that there was a significant effect of Ternate local banana culture media, in this case plantain culture media, on the fecundity of fruit fly (D. melanogaster) with a significant value of 0.014 out of 0.05. Based on this research, it can be concluded that there is a significant effect of Ternate local banana culture media on fruit fly fecundity.